Den livsoplysende tekst - Bugge, Knud Eyvin (Grundtvig-studier, 1998)
The Life-Enlightening Text By K.E. Bugge On January 30th, 1998, a Grundtvig thesis was defended at the University of Linköping in Sweden. The writer is Bosse Bergstedt, who is employed at the Institute of Pedagogics and Psychology at that university. The thesis, which runs to 368 pages, is entitled: » Den livsupplysande texten. En läsning av N.F.S. Grundtvig's pedagogiska skrifter« (The Life-Enlightening Text. A Reading of N.F.S. Grundtvig’s Educational Writings). The book is published by Carlsson’s Publishing Company in Stockholm (1998).Bosse Bergstedt’s thesis is the fourth in a series of Swedish doctoral theses on Grundtvig. With this study of the relationship between oral and written presentation in Grundtvig, Bosse Bergstedt deals with a highly central theme in his writings. With its linguistic and literary analysis of Grundtvig’s pedagogical work, the thesis represents a new approach to the study of his educational writings. Earlier, the focus of interest was primarily on the educational ideas of the texts and their origin and background.The present review begins with a detailed overview of the contents of the book, followed by a number of supplementary and critical comments. It is noted, by way of introduction, that the writer has left large parts of Grundtvig’s writings out of consideration, and some examples are given of texts that might have been profitably included. Bosse Bergstedt has made use of two unprinted texts from the Grundtvig archives, which, however, do not seem to have been quoted directly from the manuscripts. In the biographical sections there are minor errors which are primarily due to the writer’s dependence on Edvard Lehmann’s Grundtvig book, which was published in Swedish in 1927. Furthermore, the categorization used by Bosse Bergstedt in his overview of earlier research, is debatable.In spite of such critical remarks, a balanced opinion of the work must conclude on a positive note. It is an extraordinarily well-written book, and it deals with a central issue in Grundtvig’s universe. Moreover, it is greatly to the writer’s credit that his evaluations of earlier scholars and their results are cautious and well-founded. Finally, one notices his humility towards his task, as it is appears, for example, from his repeated emphasis on the enigmatic nature of the texts.